2012
DOI: 10.4161/auto.8.2.18373
|View full text |Cite
|
Sign up to set email alerts
|

Atg4 recycles inappropriately lipidated Atg8 to promote autophagosome biogenesis

Abstract: Atg8 is a ubiquitin-like protein required for autophagy in the budding yeast Saccharomyces cerevisiae. A ubiquitin-like system mediates the conjugation of the C terminus of Atg8 to the lipid phosphatidylethanolamine (PE), and this conjugate (Atg8-PE) plays a crucial role in autophagosome formation at the phagophore assembly site/pre-autophagosomal structure (PAS). The cysteine protease Atg4 processes the C terminus of newly synthesized Atg8 and also delipidates Atg8 to release the protein from membranes. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
181
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(192 citation statements)
references
References 31 publications
10
181
1
Order By: Relevance
“…The LGG-1(G116 end) transgene also rescues, although not completely, defective degradation of protein aggregates in atg-4.1; atg-4.2 double mutants. In ⌬atg4⌬atg8 yeast cells, expressing Atg8G116 also partially suppresses the defect in autophagy (35). Thus, the deconjugation activity is not completely required for autophagic flux.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The LGG-1(G116 end) transgene also rescues, although not completely, defective degradation of protein aggregates in atg-4.1; atg-4.2 double mutants. In ⌬atg4⌬atg8 yeast cells, expressing Atg8G116 also partially suppresses the defect in autophagy (35). Thus, the deconjugation activity is not completely required for autophagic flux.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study showed that yeast Atg4 also recycles Atg8-PE pro- duced on inappropriate membranes to maintain a cytoplasmic pool of unlipidated Atg8 that can undergo lipidation and participate in autophagosome formation at the pre-autophagosomal structure (PAS) (35). The mutant form of LGG-1, in which the conjugated glycine residue is directly exposed, rescues defective degradation of protein aggregates in atg-4.1 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…The exposed Gly residue is then implicated in adduct with PE. Atg4 is also required for a deconjugation step in which Atg8-PE is removed from the outer membrane of autophagosome for Atg8 recycling and autophagosome completion (7,8).…”
mentioning
confidence: 99%
“…The hydrolysis of this lipid is critical in releasing the Atg machinery from the completed autophagosome, and it appears to be requisite for the fusion of these vesicles with the vacuole (Cebollero et al 2012b). Accordingly, autophagosomes with Atg8 on their surface fuse inefficiently with the vacuole Nakatogawa et al 2012). This fusion step involves components that are common to other transport processes that terminate at the vacuole.…”
Section: Macroautophagymentioning
confidence: 99%